Persepsi Guru tentang Pelayanan Tenaga Administrasi Sekolah di SMK Negeri Kota Payakumbuh - U Pg Fitra A M; Santoso, Yulianto; Nellitawati; Achyar, Novriyanti (Global Action and Education for Society, 2024)
This study aims to analyze the service data of School Administration Personnel seen from the aspects of 1) ease of getting services, 2) certainty of service time, 3) accuracy/accuracy, 4) friendliness, 5) responsibilities carried out at SMK Negeri Kota Payakumbuh. This type of research is descriptive research. This research was conducted at SMK Negeri Kota Payakumbuh with a population of all teachers totaling 454 teachers with a sample of 84 teachers. The trial was conducted by 20 teachers outside the sample. To determine the sample size using the Slovin formula with an error rate of 10% with the Proportional Random Sampling technique. The research instrument uses the Likert Scale model with five alternative answers. Validity test using questionnaire and reliability using SPSS (Statistic Package and Social Science) 24.0 for windows program. The validity test of this study used a product moment with a significant level of 5% (0.444) with a reliability test using the Alpha Cronbach formula. The collected data is processed using the average formula (mean). The results of the data analysis showed that the service of School Administration Personnel in terms of: 1) ease of getting services obtained a score of 4.37 (good), 2) certainty of service time obtained a score of 4.43 (good), 3) accuracy/accuracy obtained a score of 4.41 (good) and 4) friendliness obtained a score of 4.31 5) responsibility obtained a score of 4.34 (good). It can be concluded that the service of School Administration Personnel at SMK Negeri Kota Payakumbuh obtained an average score of 4.37 in the good category.